The Trial of Superdebthunterbot. - KNOWLES, HELEN (Afterimage, 2023)
The article presents the exhibition review "The Trial of Superdebthunterbot" held in a small gallery in Oriel Sycharth, in Wrexham, Wales including artwork taking the form of a scripted performance.